Analysis of electro mechanical of the heart from ECG signal of subjet under exercise [electronic resource] - Abdul Rahman Ahmed Ali Salem, 1990-, author 635528; Sheikh Hussain Shaikh Salleh, 1958-, supervisor 455474; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (2015)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2015